Optimal time-based and cost-based contracts in construction projects under asymmetric information - Shi, Guanqun; Tong, Jingru; Chen, Zhiyuan; Wang, Yichen (Journal of Civil Engineering and Management, 2025)
A project owner (principal) delegates a project to a contractor (agent). Because the contractor has construction experience, he has private information about the project’s expected completion time. Besides, the contractor can exert an unobservable effort to shorten the completion time. Under an asymmetric information setting, we provide the optimal time-based contract and the optimal cost-based contract, both of which consists of one payment scheme. Additionally, we consider a menu of time-based contracts that consists of a series of contracts. By comparing three contracts, we demonstrate that the owner has a preference for the menu of time-based contracts over the other two. The pooling time-based contract is superior to the pooling cost-based contract. We also find that the social welfare under the pooling time-based contract is lower than under the menu of time-based contracts if the daily operating cost is low but it may be higher than under the menu of time-based contracts if the daily operating cost is high. For the pooling cost-based contract, whether it is better than the previous two contracts depend greatly on the proportion of cost borne by the contractor and the daily operating cost.